Microbial Community Compositional Stability in Agricultural Soils During Freeze-Thaw and Fertilizer Stress - Jensen, Grant; Krogstad, Konrad; Rezanezhad, Fereidoun; Hug, Laura A. (Frontiers in Environmental Science, 2022)
Microbial activity persists in cold region agricultural soils during the fall, winter, and spring (i.e., non-growing season) and frozen condition, with peak activity during thaw events. Climate change is expected to change the frequency of freeze-thaw cycles (FTC) and extreme temperature events (i.e, altered timing, extreme heat/cold events) in temperate cold regions, which may hasten microbial consumption of fall-amended fertilizers, decreasing potency come the growing season. We conducted a high-resolution temporal examination of the impacts of freeze-thaw and nutrient stress on microbial communities in agricultural soils across both soil depth and time. Four soil columns were incubated under a climate model of a non-growing season including precipitation, temperature, and thermal gradient with depth over 60 days. Two columns were amended with fertilizer, and two incubated as unamended soil. The impacts of repeated FTC and nutrient stress on bacterial, archaeal, and fungal soil community members were determined, providing a deeply sampled longitudinal view of soil microbial response to non-growing season conditions. Geochemical changes from flow-through leachate and amplicon sequencing of 16S and ITS rRNA genes were used to assess community response. Despite nitrification observed in fertilized columns, there were no significant microbial diversity, core community, or nitrogen cycling population trends in response to nutrient stress. FTC impacts were observable as an increase in alpha diversity during FTC. Community compositions shifted across a longer time frame than individual FTC, with bulk changes to the community in each phase of the experiment. Our results demonstrate microbial community composition remains relatively stable for archaea, bacteria, and fungi through a non-growing season, independent of nutrient availability. This observation contrasts canonical thinking that FTC have significant and prolonged effects on microbial communities. In contrast to permafrost and other soils experiencing rare FTC, in temperate agricultural soils regularly experiencing such perturbations, the response to freeze-thaw and fertilizer stress may be muted by a more resilient community or be controlled at the level of gene expression rather than population turn-over. These results clarify the impacts of winter FTC on fertilizer consumption, with implications for agricultural best practices and modeling of biogeochemical cycling in agroecosystems.